Structural basis for the flexible recognition of α‐glucan substrates by Bacteroides thetaiotaomicron SusG. (17th April 2018) - Arnal, Gregory; Cockburn, Darrell W.; Brumer, Harry; Koropatkin, Nicole M.
Abstract: Bacteria that reside in the mammalian intestinal tract efficiently hydrolyze dietary carbohydrates, including starch, that escape digestion in the small intestine. Starch is an abundant dietary carbohydrate comprised of α1, 4 and α1, 6 linked glucose, yet mammalian intestinal glucoamylases cannot effectively hydrolyze starch that has frequent α1, 6 branching as these structures hinder recognition and processing by α1, 4‐specific amylases. Here we present the structure of the cell surface amylase SusG from Bacteroides thetaiotaomicron complexed with a mixed linkage amylosaccharide generated from transglycosylation during crystallization. Although SusG is specific for α1, 4 glucosidic bonds, binding of this new oligosaccharide at the active site demonstrates that SusG can accommodate α1, 6 branch points at subsite −3 to −2, and also at subsite+1 adjacent to the site of hydrolysis, explaining how this enzyme may be able to process a wide range of limit dextrins in the intestinal environment. These data suggest that B. thetaiotaomicron and related organisms may have a selective advantage for amylosaccharide scavenging in the gut. Abstract : PDB Code(s):6BS6